Hearing and Vision Screening Program for newborns in Italy - Bubbico, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The aims of this paper were to present data on the implementation and coverage of simultaneous Universal Neonatal Hearing and Vision Screening programmes and to evaluate the organization and management of these healthcare procedures in Italy.Materials and Methods. Data were collected through a nationwide survey conducted in 2018. All maternity wards active in Italy in 2017 were included. Results. Hearing screening. Overall 427,365 newborns out of 448,386 (95.3%) received the hearing screening test (first level) in 391 out of the 409 maternity hospitals (95.5%), with a national mean referral rate of 3.63% (SD ± 4.58). A statistically significant increase (p